A new species of Nysson Latreille (Hymenoptera: Crabronidae: Bembicinae) from Turkmenistan - Nemkov, Pavel G.; Gayubo, Severiano F. (Zootaxa, 2003)
Nysson kazenasi sp. nov. from Turkmenistan is described and illustrated. It differs from all known species of Nysson in having the hypoepimeral area strongly swollen like a hollow longitudinal conical- shaped structure.